Meningkatkan Profitabilitas Bank Umum Syariah di Indonesia Melalui Islamicity Performance Index dan Operating Eficiency Ratio - Ibrahim Ibrahim; Asbi Amin; Rostiaty Yunus; Hasyim Mochtar (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to examine the effect of Islamicity Performance Index and Operating Efficiency Ratio on Profitability at Islamic Commercial Banks in Indonesia. This research is a quantitative study, used with the ultimate goal of arriving at a resolution of the proposed theory by dissecting quantitative information. The population of this study is all Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK) in 2016-2020, namely 14 BUS as the population in this study. Then, purposive sampling is used with the following criteria: 1) Sharia banking financial statements published successively during the period 2016, 2017, 2018, 2019, 2020 and 2021; 2) Financial statements that do not suffer losses; 3) Presenting the data needed in this study. So that the number of samples is determined to be 36 data from 6 Islamic Commercial Banks. The econometric model used is a panel data regression analysis model using the Eviews 12 application. The results found that Profit Sharing Ratio (PSR) and Operating Efficiency Ratio (OER) had a significant negative effect on Return On Assets (ROA). Meanwhile, Islamic Income Ratio (IsIR) and Zakat Performance Ratio (ZPR) did not have a significant effect on Return On Assets (ROA).